PENGARUH KADAR INHIBITOR EKSTRAK KULIT BUAH RAMBUTAN DAN KONSENTRASI LARUTAN HCL TERHADAP LAJU KOROSI BAJA ST 37 - muhammad salafudin bukhori; Ranto Ranto; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
Industrial manufacture of steel with pickling process method uses HCl solution as a cleaner. Besides as a cleaner, HCl solution can also causes a corrosion on steel product from pickling process. That corrosion can be controlled by corrosion inhibitor from organic material. Organic material consist of tannin compound that can react by forming a complex compound on the steel surface and protect it from corrosion attack. Organic material in this research is rambutan peel extract used as inhibitor corrosion with the values of 0.5%, 1.0%, 1.5%, and 2.0% in HCl solution with the values of 0.1 N, 0.5 N, and 1.0 N. St 37 steel is used as test sample in this research. The aims of this research are to investigate the effect of amount of rambutan peel extract and concentration of HCl solution toward the corrosion rate of St 37 steel. Weight loss method is used to calculate the corrosion rate and Two Way Anova is used as data analysis technique. The result of this research shows that there is an effect of the amount of rambutan peel extract as an inhibitor and concentration of HCl solution toward the corrosion rate of St 37 steel. Corrosion rate has the lowest value in the variation of 2.0% inhibitor and 0.1 N HCl with the highest efficiency value as 63.13%.